Recepción de la Teoría Crítica en América Latina: la constelación benjaminiana de marxismo y teología en Franz Hinkelammert - Estela Fernández Nadal (Franciscanum, 2012)
The article analyzes the relation between theology and historical materialism in Franz Hinkelammert and Walter Benjamin. From the consideration of diverse writings of both philosophers, important points of meeting appear between them, particularly concerning to the analysis of the links between Christianity and Modernity, Modernity and capitalism, Utopian tendency and Messianic redemption. Besides, the role that both authors assign to the myths of domination and emancipation is emphasized within the constitution of modern societies.